To compare the efficacy and safety of Rosuvastatin, Atorvastatin and Pravastatin among dyslipidemic diabetic patients at a tertiary centre in Bihar (Journal of Pharmaceutical Negative Results, 2023)
Background: The "coronary heart disease risk equivalent" of diabetes is now widely accepted as a medical fact. This is mostly attributable to the prevalence of dyslipidemia in the diabetic population, which is thought to be a primary contributor to the disproportionately high number of fatalities in this group caused by cardiovascular disease.Aim and objectives: To compare the efficacy and safety of rosuvastatin, atorvastatin and pravastatin among dyslipidemic diabetic patients.Materials and methods: 90 men and women with type II diabetes. People were divided up into groups. Atorvastatin 20 mg was given to Group 1 patients, rosuvastatin 20 mg was given to Group 2, and pravastatin 20 mg was given to Group 3. Total cholesterol, good cholesterol (HDL), bad cholesterol (LDL), and triglyceride (TG) levels were all assessed. The metric for safety was also evaluated.Results: In groups 1, 2, and 3, the mean percent reduction in LDL was -20.02, -30.78, and -11.02, respectively. TG was reduced by -20.87, -26.11, and -13.22 in groups 1, 2, and 3, respectively. TC was -14.11, -23.14, and -16.14 in groups 1, 2, and 3, respectively, and the percentage increase in HDL was -6.55, -5.11, and -6.41 in groups 1, 2, and 3, respectively. The difference was significant (P< 0.05). No patients in the current study showed elevated ALT levels greater than 3, the upper limit of normal. So far, none of the statins used in the study have been associated with any adverse events that could have affected hepatic function.Conclusion: Rosuvastatin, in contrast to atorvastatin and pravastatin, was shown to be the most effective statin in lowering LDL-C.